Net clinical benefit of edoxaban versus no treatment in a 'real world' atrial fibrillation population: A modelling analysis based on a nationwide cohort study. (15th December 2015) - Blann, Andrew D.; Banerjee, Amitava; Lane, Deirdre A.; Torp-Pedersen, Christian; Lip, Gregory Y.H.
Abstract: Background: In non-valvular atrial fibrillation (AF), oral anticoagulation reduces the risk of thromboembolism such as stroke and systemic embolism (SSE), but increases the risk of major bleeding such as intracranial haemorrhage (ICH). The risk-benefit balance between SSE versus ICH can be expressed as the net clinical benefit (NCB); however, the risk of SSE and ICH varies according to clinical factors that can be assessed using CHADS2, CHA2 DS2 -VASc (both quantifying risk of stroke) and HAS-BLED (quantifying risk of major bleeding) scores, respectively. Methods: Using established modelling based on event rates for thromboembolism and haemorrhage in the Danish nationwide cohort study, we tested the hypothesis that edoxaban has a superior NCB compared with warfarin. Results: In our overall model, compared to no treatment, warfarin had a NCB of 0.26 (95% CI 0.24, 0.28) events prevented per 100 patient years, edoxaban 60 mg daily a NCB of 0.71 [0.69, 0.76], and edoxaban 30 mg daily a NCB of 0.71 [0.0.68, 0.73]. When compared to no treatment, both doses of edoxaban have superior NCB values than those of warfarin at all CHADS2 and CHA2 DS2 -VASc scores. At CHADS2 ≥ 2 and CHA2 DS2 -VASc ≥ 2, edoxaban 60 mg dose had a better NCB than the 30 mg dose or warfarin, when compared to no treatment. With HAS-BLED score ≥ 3, both doses of edoxaban had a positive NCB compared to warfarin, at CHADS2 or CHA2 DS2 -VASc ≥ 2. Conclusion: Our modelling study suggests that both 30 mg and 60 mg doses of edoxaban have a favourable NCB compared to warfarin, and the degree of benefit differs according to CHADS2, CHA2 DS2 -VASc and HAS-BLED scores. At CHA2 DS2 -VASc score ≥ 2, both edoxaban doses were superior to warfarin, but compared to no treatment, the 60 mg dose had a better NCB than the 30 mg dose or warfarin.